RELATIONSHIP BETWEEN RISK FACTORS AND PERIODONTAL DISEASE AMONG PATIENTS IN COMMUNITY HEALTH CENTERS - A'yun, Quroti; Risnawati, Dewi; Subekti, Ani (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Periodontal disease is an infection in the oral cavity that is often found in the community and is considered as the number two disease in the world after dental caries. The higher the age, the higher the index of periodontal disease and if no prevention is carried out it can affect a person's quality of life. This study aims to determine the relationship between risk factors and the occurrence of periodontal disease.Method: This type of research is observational with a cross-sectional design. The sample in this study was taken by proportional random sampling and it was obtained as many as 250 patients aged 15-55 years. The risk factors studied were: OHI-S index, instantaneous blood sugar, knowledge of periodontal disease, dental and oral health maintenance behavior, food selection behavior, smoking habit, and utilization of health services. Measurement of periodontal disease based on the state of gingival infection and the data were analyzed using the chi-square test.Result: The results of the chi-square test obtained the OHI-S index, knowledge of periodontal disease, dental and oral health maintenance behavior, food selection behavior, personal blood sugar, and utilization of dental health services (p<0.05). The relationship between smoking habits and the occurrence of periodontal disease was p>0.05Conclusion: the risk factors: OHI-S, knowledge of periodontal disease, dental and oral health maintenance behavior, food selection behavior, instantaneous blood sugar levels, and utilization of dental and oral health services are significantly associated with the occurrence of periodontal disease.